Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Show that. (4pq + 3q)^2– (4pq – 3q)^2 = 48pq^2 Show that. (4pq + 3q)^2– (4pq – 3q)^2 = 48pq^2

Show that.
(4pq + 3q)^2– (4pq – 3q)^2 = 48pq^2
Show that.
(4pq + 3q)^2– (4pq – 3q)^2 = 48pq^2

Grade:12

1 Answers

Anand Kumar Pandey
askIITians Faculty 5733 Points
2 months ago
Dear Student

LHS = (4pq + 3q)^2– (4pq – 3q)^2
=16p^2q^2+ 24pq^2+ 9q^2- 16p^2q^2+ 24pq^2- 9q^2= 48pq^2
RHS = 48pq^2
LHS = RHS

Thanks

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free